2014
DOI: 10.1186/1756-3305-7-30
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection of Dirofilaria immitis, Dirofilaria repens and Setaria tundra in mosquitoes from Germany

Abstract: BackgroundAs a result of globalization and climate change, Dirofilaria immitis and Dirofilaria repens, the causative agents of dirofilariosis in Europe, continue to spread from endemic areas in the Mediterranean to northern and northeastern regions of Europe where autochthonous cases of dirofilarial infections have increasingly been observed in dogs and humans. Whilst D. repens was recently reported from mosquitoes in putatively non-endemic areas, D. immitis has never been demonstrated in mosquitoes from Europ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
67
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(79 citation statements)
references
References 38 publications
4
67
0
4
Order By: Relevance
“…Recently, Tappe et al (2014) described the first autochthonous human case in Germany, after a series of cases in dogs in previous years had indicated the occurrence of D. repens there (Hermosilla et al 2006, Sassnau et al 2009). Since the parasite has also been repeatedly detected in a local mosquito population in Germany, a stable local transmission is now assumed (Czajka et al 2014;Kronefeld et al 2014). Adult D. repens live and mate mainly in the subcutaneous tissue and perimuscular fasciae and female worms release their offspring, the microfilariae (MF), into the blood stream.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Tappe et al (2014) described the first autochthonous human case in Germany, after a series of cases in dogs in previous years had indicated the occurrence of D. repens there (Hermosilla et al 2006, Sassnau et al 2009). Since the parasite has also been repeatedly detected in a local mosquito population in Germany, a stable local transmission is now assumed (Czajka et al 2014;Kronefeld et al 2014). Adult D. repens live and mate mainly in the subcutaneous tissue and perimuscular fasciae and female worms release their offspring, the microfilariae (MF), into the blood stream.…”
Section: Introductionmentioning
confidence: 99%
“…vexans (Kronefeld et al 2014). However, the pathogenic potential of Setaria for free-living animals (e.g.…”
Section: Resultsmentioning
confidence: 98%
“…Taking into account the long flying distance (migrations of up to 15 km), this species becomes suitable for local transmission and the spread of zoonotic dirofilariosis into new endemic foci. Outside the traditional Mediterranean distribution area, dirofilarial worms have also recently been described in mosquitoes from Slovakia (Bocková et al 2013), Austria (Silbermayr et al 2014) and Germany (Czaijka et al 2014;Kronefeld et al 2014), the more so as in two of the four cases (Bocková et al 2013;Czajka et al 2014) Ae. vexans was involved.…”
Section: Resultsmentioning
confidence: 98%
“…In neighbouring Portugal, Cx. pipiens revealed a higher D. immitis infection rate (0.5%) , while in Italy, the prevalence rates for this species range between 0.05% and 0.54% Latrofa et al, 2012), being lower (0.12%) in Turkey (Yildirim et al, 2011) or in Germany (0.02%) (Kronefeld et al, 2014), but reaching as high as 1.49% in Hungary (Zittra et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…pipiens. Kronefeld et al (2014) suggested the presence of Cardiofilaria pavlovskyi on mosquitoes in Germany. Curiously, this species has also been previously reported in birds in Spain by López-Caballero (1982).…”
Section: Discussionmentioning
confidence: 99%